The Role and Significance of Forest on Climate Change and Economy in Pakistan - Romesa Najeeb; Fazeel Ashraf Qaisrani; Dr.Sohail Akhtar; Iqra Nazeer (Al-Qanṭara, 2023)
Forests refer to the area of the earth where trees are abundant. Realizing the economic and environmental importance of forests makes their presence valuable. At present, forests are very important for human and animal life, but still, deforestation continues without any thought, which is dangerous for the human environment. The Forests of a country mostly depend on a suitable climate and temperature along with a good ratio of the amount of rainfall. With all this, the type and condition of soil it possesses for growth. In Pakistan, various types of forests are found in different areas. This is an analytical-based study about the role of forests in the economy. Among the various traditional sources of income, forests are also considered a very important source of earning from the prehistoric period of mankind. Man used wood for fire to cook food and its wooden articles for earning. In the modern era of development, forests are considered a sign of prosperity for a country and play a very important role in the atmospheric and climatic change of society on a global level. Although Pakistan is recognized as an agrarian country and agriculture is the major tool of the economy, Pakistan needs more forest, which has always proved seriously fatal for the environment of the country. Primarily this paper deals with and explores the role of forests in the economy of Pakistan after its emergence. The following paper deals with and explores the nature, importance and role of forests in the atmospheric condition and economy of Pakistan.